2004
DOI: 10.1029/2004jd004963
|View full text |Cite
|
Sign up to set email alerts
|

Cross‐validation of MIPAS/ENVISAT and GPS‐RO/CHAMP temperature profiles

Abstract: [1] The Michelson Interferometer for Passive Atmospheric Sounding (MIPAS) on board the ENVISAT and the Global Positioning System (GPS) receiver on the Challenging Mini-Satellite Payload (CHAMP) provide temperature profiles by limb-viewing midinfrared emission and radio occultation (RO) measurements, respectively. The MIPAS temperatures retrieved at the Institut für Meteorologie und Klimaforschung (IMK) are compared with the GPS-RO/CHAMP observations derived at Jet Propulsion Laboratory (JPL) and GeoForschungsZ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
36
0

Year Published

2004
2004
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 36 publications
3
36
0
Order By: Relevance
“…A similar study was performed by Kuo et al (2005). A cross-validation of MI-PAS/ENVISAT and CHAMP RO temperature profiles for 2 weeks in September/October 2002 shows global mean differences averaged between 8 and 30 km of less than 0.1 K (Wang et al, 2004). For the data quality of SAC-C temperature we refer to an intercomparison study for CHAMP and SAC-C (Hajj et al, 2004) that showed for nearby profiles (distance d≤200 km and time delay t ≤30 min) an agreement within 0.1 K in the mean between 5 and 15 km altitude.…”
Section: Validation Of Champ/sac-c Temperature Datamentioning
confidence: 98%
“…A similar study was performed by Kuo et al (2005). A cross-validation of MI-PAS/ENVISAT and CHAMP RO temperature profiles for 2 weeks in September/October 2002 shows global mean differences averaged between 8 and 30 km of less than 0.1 K (Wang et al, 2004). For the data quality of SAC-C temperature we refer to an intercomparison study for CHAMP and SAC-C (Hajj et al, 2004) that showed for nearby profiles (distance d≤200 km and time delay t ≤30 min) an agreement within 0.1 K in the mean between 5 and 15 km altitude.…”
Section: Validation Of Champ/sac-c Temperature Datamentioning
confidence: 98%
“…Based on these measures, CCR aims to extend the altitude range of reliable, accurate retrieval results (currently up to about 25 km; see Sect. 4; Wang et al, 2004;Wickert et al, 2004;von Engeln, 2006) towards the upper stratosphere (up to about 35 km). The development of the algorithmic basis and careful performance assessment via end-to-end simulation studies by Gobiet and Kirchengast (2004) and Steiner and Kirchengast (2005) have demonstrated that this improvement potential exists.…”
Section: Retrieval Of Ro Temperature Profilesmentioning
confidence: 99%
“…Evaluation studies showed that RO temperatures are generally derived with an accuracy of better than 1 K (e.g., Hajj et al, 2002;Wickert et al, 2004;Steiner et al, 2004) though it has also been found that RO retrieval results of major processing centres show, compared to other remote sensing instruments, radiosondes, and amongst themselves, biases exceeding 1 K above 25 km (e.g., Wang et al, 2004;Wickert et al, 2004;von Engeln, 2006) which is mainly due to the methodology of integrating a priori information in the highaltitude initialisation of the retrieval process as will be discussed in this study. Biases induced by downward propagated a priori information are a particular concern for climate applications like, e.g., long-term trend studies, since a priori data (often meteorological analyses) are on one hand particularly prone to model errors due to sparse observational data at high altitudes, and on the other hand they are far from long-term stable due to frequent model, observational data, and data assimilation system changes and improvements.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Steiner et al, 2007;Gobiet et al, 2007;Wickert, 2004a;Wang et al, 2004;Hajj et al, 2004). Special comparisons of tropopause parameters between CHAMP and ECMWF can be found in, e.g.…”
Section: Introductionmentioning
confidence: 99%